Implementasi Sistem Rekomendasi Mitigasi Layanan Sertifikasi Produk Halal Berbasis Blockchain pada LP UMKM Muhammadiyah Kota Semarang - Amri, Saeful; M. Al Haris; Purnomo Putro, Dwi; Mandala Adikara Sencoko (LOSARI DIGITAL, 2025)
The Muhammadiyah Regional Leadership (PDM) of Semarang City has an MSME Development Institute (LP). This institution has a specific mission in developing MSMEs in growing, mobilizing, improving and empowering the potential of MSMEs in the national and global business arena. This community service activity is to implement a distributed system to develop the creative industry and encourage entrepreneurship in the field of digital technology and innovation and can increase responsible consumption and production in terms of halal consumer products for Muhammadiyah MSMEs in Semarang City. This activity includes socialization, training on system operation, implementation, mentoring and monitoring. The results show that the implementation of the system can document the data of MSMEs well by 75%, halal product certification for MSMEs increased by 80%, and skills in operating the system are increasing, based on the satisfaction level reaching 91% after the activity. This program proves that utilizing technology can provide convenience in verifying data for the halal certification process and increase security and reduce the risk of data loss.